Case report: Bullous pemphigoid arising in a patient with scleroderma and multiple sclerosis - Moro, Francesco; Mariotti, Feliciana; Pira, Anna; De Luca, Naomi; Didona, Biagio; Pagnanelli, Gianluca; Di Zenzo, Giovanni (Frontiers in Medicine, 2022)
Background Bullous pemphigoid (BP) is the most common autoimmune blistering disease, clinically characterized by erythematous urticarial plaques, blisters and intense pruritus, induced by autoantibodies against two proteins of the dermo-epidermal junction BP180 and BP230. Among BP comorbidities a high number of autoimmune diseases are reported in literature such as multiple sclerosis, but only few cases in association with scleroderma and none in association with both. Case presentation We present the case of a 68 years old woman affected by multiple sclerosis and scleroderma who developed a severe bullous pemphigoid with a bullous pemphigoid disease area index of 60 and high titers of anti-BP180 and anti-BP230 autoantibodies by ELISA. After 2 months of therapy with both intravenous and oral corticosteroids the active lesions of bullous pemphigoid remitted with no relapse. Conclusion Autoimmune diseases affecting the skin or organs where BP180 and BP230 are present could trigger through an epitope spreading phenomenon an immune response to these antigens and, over years, induce bullous pemphigoid onset.